Assessment and management of the malignant colorectal polyp. Issue 2 (6th March 2015) - Neilson, Laura J; Rutter, Matthew D; Saunders, Brian P; Plumb, Andrew; Rees, Colin J
Abstract : Colorectal cancer is the second most common cancer affecting men and women in England. The introduction of National Bowel Cancer Screening in 2006 has led to a rise in the proportion of colorectal cancers detected at an early stage. Many screen-detected cancers are malignant colorectal polyps and may potentially be cured with endoscopic resection, without recourse to the risk of major surgery or prolonged adjuvant therapies. Endoscopic decision making is crucial to select those early lesions that may be suitable for local endoscopic excision as well as identifying lesions for surgical resection, thus avoiding unnecessary surgical intervention in some and ensuring potentially curative surgery in others. This paper uses the current evidence base to provide a structured approach to the assessment of potentially malignant polyps and their management. http://group.bmj.com/products/journals/instructions-for-authors/licence-forms